Matrix metalloproteinase‐9, 10, and stress hyperglycaemia in acute kidney injury. (14th June 2018) - Guvercin, Guray; Karakus, Volkan; Aksit, Murat; Dere, Yelda; Aktar, Merve; Alpay, Hasan; Bozkaya, Giray; Tatar, Erhan
Abstract: Background: This study investigated the effect of matrix metalloproteinase (MMP)‐9 and 10, and stress hyperglycaemia on the necessity of emergency renal replacement therapy (RRT) and mortality in nondiabetic geriatric patients with acute kidney injury (AKI). Materials and Methods: The present observational and longitudinal study included 101 nondiabetic geriatric patients (age >65 years) with AKI. The serum levels of MMP‐9 and MMP‐10 were evaluated in these patients. Serum glucose level >140 mg/dL at the time of admission was accepted as stress hyperglycaemia. Results: The average age of patients was 81 ± 7.1 years. Stress hyperglycaemia was diagnosed in 34.6% of the cases; the majority of these cases were patients with high‐serum urea, CRP, and chronic kidney disease. The average levels of MMP‐9 and MMP‐10 were found to be 199 ± 38 and 16.5 ± 7.5 ng/mL, respectively. Thirty‐one cases (30.6%) mortality during hospitalization and 20 cases (20%) underwent emergency RRT. Multiregression analysis showed the serum urea ( P < .001) and stress hyperglycaemia ( P = .03) to be independently associated with mortality. Also, serum urea ( P = .01), potassium level ( P = .03), and MMP‐10 levels ( P = .03) were independently associated with the necessity of the emergency RRT. The MMP‐9 levels exhibited no relation with the necessity of emergency RRT and mortality. Conclusion: Stress hyperglycaemia is a common condition among nondiabetic geriatric patients with AKI and is related to mortality. Serum MMP‐10 levels serve as an important predictor of the necessity of emergency RRT in these patients.